2003
DOI: 10.1038/sj.onc.1206072
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia-related transcription factor TEL accelerates differentiation of Friend erythroleukemia cells

Abstract: TEL belongs to a member of the ETS family transcription factors that represses transcription of target genes such as FLI-1. Although TEL is essential for establishing hematopoiesis in neonatal bone marrow, its role in erythroid lineage is not understood. To investigate a role for TEL in erythroid differentiation, we introduced TEL into mouse erythroleukemia (MEL) cells. Overexpressing wild-type-TEL in MEL cells enhanced differentiation induced by hexamethylene bisacetamide or dimethylsulfoxide, as judged by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…The C-terminal ETV6 mutations were either inframe or resulted in truncation of the ETS domain by out-of-frame mutation. In concordance with earlier studies (Waga et al, 2003;Wood et al, 2003), the truncated ETV6 proteins were impaired in repressing transcription in a ETV6-specific luciferase assay. Moreover, coexpression of the mutants with an intact homodimerization domain (#2236, 3102, 2649 and N) completely abolished the transcription repression by wt ETV6.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The C-terminal ETV6 mutations were either inframe or resulted in truncation of the ETS domain by out-of-frame mutation. In concordance with earlier studies (Waga et al, 2003;Wood et al, 2003), the truncated ETV6 proteins were impaired in repressing transcription in a ETV6-specific luciferase assay. Moreover, coexpression of the mutants with an intact homodimerization domain (#2236, 3102, 2649 and N) completely abolished the transcription repression by wt ETV6.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, ETV6 has been shown to stimulate erythroid differentiation of the murine erythroid leukemia cell line (Waga et al, 2003). ETV6 knockout mice are embryonic lethal at days 10.5-11.5 and exhibit defects in yolk sac angiogenesis and intraembryonic apoptosis of mesenchymal and neural cells.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of plasmid pCXN2-FLAG-TEL was described in a previous study. (20) To establish stable transfectants, 1 × 10 7 of UT-7/GM cells were electroporated with 20 µg of pCXN2-FLAG-TEL at 380 V and 975 µF using Gene Pulser (Bio-Rad, Hercules, CA). Transfected cells were selected with 0.8 mg/mL of G418 (Sigma-Aldrich, St. Louis, MO) and cloned by limiting dilution.…”
Section: Methodsmentioning
confidence: 99%
“…(19) As for lineage-specific roles in hematopoietic systems, we have reported that TEL accelerates erythroid differentiation of mouse erythroleukemia (MEL) cells induced by hexamethylene bisacetamide (HMBA) or dimethylsulfoxide (DMSO). (20) Because both erythroblasts and megakaryocytes arise from common progenitors, this observation prompted us to search for TEL's roles in lineage commitment of the bi-potential progenitors.…”
mentioning
confidence: 99%
“…Such dual effects, transactivation or repression of different target genes by one transcription factor, have previously been described for other transcription factors likewise among which are members of the ETS family (65)(66)(67)(68)(69)(70)(71)94).…”
Section: Discussionmentioning
confidence: 99%